Analisis Kualitas Pelayanan Terhadap Kepuasan Nasabah PT. WOM Finance Wonogiri - Aris Susanto; Bambang Mursito; Sri Hartono (ITB AAS INDONESIA Surakarta, 2019)
Analysis of Service Quality Towards Customer Satisfaction PT. WOM Finance Wonogiri. Thesis, Management Study Program (S1). Surakarta Batik Islamic University, 2019. This study aims to determine the effect of service quality consisting of tangibles, reliability, responsiveness, assurance, empathy simultaneously and partially on customer satisfaction at PT WOM Finance Wonogiri.. This research uses quantitative research methods. Data sources used in this study were respondents or people who responded or answered the researchers' questions, namely customers of PT. WOM Finance Wonogiri. Data collection methods used observation, questionnaire, and documentation. This study uses classical assumption test techniques, multiple linear regression analysis, and hypothesis testing (t test,f test, and coefficient of determination). The results of data analysis obtained there are tangibles,reliability, responsiveness, assurance,empathy effect simultaneously and partially to customer satisfaction at PT WOM Finance Wonogiri. Keywords: tangibles, reliability, responsiveness, assurance, empathy (empathy), customer satisfaction